Inhibition of Autophagy in Microglia Alters Depressive-Like Behavior via BDNF Pathway in Postpartum Depression - Tan, Xiaoning; Du, Xiaoxue; Jiang, Yuting; Botchway, Benson O. A.; Hu, Zhiying; Fang, Marong (Frontiers in Psychiatry, 2018)
Postpartum depression (PPD) is associated with mood disorders and elevated inflammation. Studies have evidenced activation/inhibition of autophagy and excessive activation of microglia to have a close relationship with depression. C57 and microglia-specific autophagy deficient mice (Cx3Cr1Cre/+ATG5loxp/loxp) were employed to establish chronic unpredicted mild stress depression mice model from embryonic day 7 (E7) to embryonic day 16 (E16). Fluoxetine was administered for 3 weeks (commencing from 1 week after birth). Behavioral tests (open field, forced swimming and sucrose preference tests) were implemented. Western blot and immunofluorescence staining were employed in assessing brain-derived neurotrophic factor (BDNF) expression level, autophagy-associated proteins and inflammatory factors. Depressive behavior was reversed following fluoxetine treatment; this was evidenced via open field, sucrose preference and forced swimming tests. Both Brain-derived neurotrophic factor (BDNF) and autophagy-associated proteins (ATG5, beclin-1 and LC3II) were upregulated following fluoxetine treatment. Inflammatory factors [Nuclear factor kappa B (NF-κB) and inducible nitric oxide synthase (iNOS)] were reduced whiles anti-inflammatory factor interleukin-10 (IL-10) was increased. Microglia-specific autophagy deficient mice (Cx3Cr1Cre/+ATG5loxp/loxp) showed curtailed autophagy level, higher inflammatory level and reduced BDNF standard when compared with C57 mice. Autophagy inhibition in microglia contributes to inflammation, which further instigates postpartum depression. Fluoxetine might mediate its anti-depressant effect in postpartum depression through the autophagic pathway, whilst upregulating BDNF expression level. In view of this, regulating BDNF in microglia is a potential novel therapy target for postpartum depression.